Prevalence and factors associated with successful treatment of hypertension in sub-Saharan Africa: a meta-analysis - Mukwena, Phanose; Mamba, Martin; Munyinda, Kandiye; Chandika, Natasha; Claudine, Christine; Kazonga, Eustarckio; Nkhama, Emmy (International Journal Of Community Medicine And Public Health, 2024)
Hypertension is a growing public health challenge in sub-Saharan Africa (SSA). However, the evidence on the prevalence and factors associated with successful treatment outcome of hypertension among adults in SSA is scarce and inconsistent. We conducted a systematic review and meta-analysis of observational studies that reported on the prevalence and/or factors associated with successful treatment outcome of hypertension among adults in sub-Saharan Africa. The aim of this study was to provide a comprehensive and updated summary of the evidence on this topic and to identify potential sources of heterogeneity among the studies. We searched databases such as PubMed, Embase, National Institute of Health, CINAHL, and Scopus for studies conducted on the prevalence and factors associated with successful treatment of hypertension in sub-Saharan Africa. We searched for articles published in English from 2014 to 2024. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines was followed. Analysis was done using Meta XL version 5.3. Twenty-four studies were included in the analysis; eighteen were conducted in Ethiopia. The pooled prevalence of uncontrolled hypertension was 54% (95% CI: 0.48-0.60) with a high heterogeneity observed among the studies (I2=97%). Factors associated with treatment outcomes included gender, adherence to medication, obesity, and physical activity. This study revealed that there was a significant association between sex, adherence to medication, physical activity and obesity and hypertension treatment outcome.